Acquisition of English morphosyntactic features of past and non-past tense and agreement by adult L1 Arabic speakers - Ali Muftah, Muneera Yahya (2011)
This study investigates the acquisition of the English morphosyntactic features of past and non-past tense and agreement by adult L I Arabic speakers within the Minimalist Program framework. In particular, the focus is on the acquisition of the verbal functional categories of T and Agr, the formal features of [±finite, ±past, ±Agr], the feature strength of T [±strong] as well as verb movement that accounts for the placement of the verb with respect to negation, adverbs and subject floating quantifiers (FQs) in finite and non-finite contexts with thematic, be auxiliary and copula be verb forms. The morphemes being examined are the third person singular agreement morpheme -s, the past tense agreement morpheme -ed, the irregular past tense and the be auxiliary and copula be verb forms of is, am, are, was and were. The study tests three competing proposals about the representation of functional categories and features in L2 acquisition: the Failed Functional Features Hypothesis (FFFH) (Hawkins and Chan, 1997), the Full Transfer Full Access (FTF A) hypothesis (Schwartz and Sprouse, 1994; 1996) and the Missing Surface Inflection Hypothesis (MSIH) (Prevost and White, 2000). The FFFH holds that the functional categories and features are inaccessible to L2 learners after the critical period as instantiation of these categories has ceased to operate due to the partial availability of Universal Grammar (UO). Therefore, the interlanguage (lL) syntactic representations in post-critical period L2 acquisition diverge from the target grammar despite apparent native-like performance (Hawkins and Chan, 1997). On the other hand, the MSIH claims that the functional categories and features are accessible to L2 learners; however, their failure to produce the required overt morphology is due to complexity in mapping between surface forms and underlying abstract features. Thus, the IL syntactic representations in post critical period L2 acquisition can be native-like and the lack of morphological forms in the IL reflects a problem with the realization of surface morphology, rather than impairment in the domain of functional representations (Prevost and White, 2000). The third proposal, the FTF A hypothesis proposes that the functional categories and features are accessible to L2 learners after the critical period. The L2 learners start out with the parameter settings instantiated in their L1 grammars (full transfer) and that they can subsequently reset parameters to the target L2 settings (due to the full accessibility of UO). Therefore, their IL representations can be native-like due to convergence on native-like representations (Schwartz and Sprouse 1994; 1996). Altogether, 240 adult Ll Arabic speakers of L2 English participated in the study. They were subdivided into three proficiency levels (lower-intermediate, upper-intermediate and advanced). The test instruments consisted of the Oxford Placement Test (OPT), two judgement tasks, a Grammaticality Judgement Task on tense and agreement (GJT1) and a Grammaticality Judgement Task on verb movement (GJT2), and two production tasks, an Elicited Written Production Task (EWPT) and an Oral Production Task (ORPT). These tasks were designed to test the learners' underlying knowledge of English past and non-past tense and agreement as well as the placement of verbs with three of the properties subsumed under the verb movement parameter including negation, adverbs and subject floating quantifiers, in finite and non-finite contexts with thematic, be auxiliary and copula be verb forms. The findings suggest that while the Arabic speakers were able to acquire the surface structure of the English tense and agreement, they nevertheless had not acquired the underlying associated features. Such findings are consistent with the view that parameterized functional features are subject to a critical period. Accordingly, the IL of the Arabic speakers is non-target like in the syntactic domain, particularly with those functional categories and associated features not instantiated in the L2 learners' Ll. These findings seem to show that the learners' IL grammars are UG-constrained, although UG is only partially available to adult L2 learners; that is, the L2 learners' IL, specifically that of the functional features, is constrained by what is available in the learners' L1.